Evaluation of a Passive Direct Greenhouse Solar Dryer under Varying Load Conditions - Rahman, Abdul; Misaran, Mohd Suffian; Ming, Chu Chi; Mansa, Rachel Fran; Jin, Tham Heng; Radzali, Mohd Adzrie; Wan Ibrahim, Mohd Kamel; Rahman, Md. Mizanur (International Journal of Integrated Engineering, 2026)
This study evaluates the thermal and drying performance of a passive direct greenhouse‑type solar dryer using synthetic sponge as a controlled model for porous biological materials. Sponge was selected to eliminate the variability in size, porosity, and initial moisture content typical of agricultural products and thereby isolate the effects of load density and spacing on heat–mass transfer. Experiments were conducted over three days. Experimental data such as solar irradiance, temperature profiles, and drying kinetics were recorded while open‑sun drying (OSD) act as control. Average solar irradiance ranged from 657–734 W m⁻², while drying efficiencies of the passive system varied between 76–86%, substantially exceeding OSD (≈ 30%). On Day 1, 5‑inch inter‑sponge spacing produced the highest chamber temperature (43.25 °C) but less uniform moisture removal. In contrast, 1‑inch spacing on Day 3 enhanced thermal stratification (ΔT ≈ 17.5 °C) and yielded quantitatively uniform drying across trays. The final moisture ratios of top 0.004 (99.6% removed), middle 0.110 (89.0%), and bottom 0.067 (93.3%). Findings show that inter-sponge spacing critically governs convective heat transfer and internal heat retention. It demonstrates that passive greenhouse dryers can maintain high efficiency and near‑uniform drying under moderate solar input. Based on the airflow–thermal response, it is recommended to have tight lateral inter‑piece spacing (~1 inch) to increase vapor residence time and internal heat retention. Also, used in conjunction with the T‑shaped enclosure’s continuous roof outlets (0.4 m × 2.5 m) and four low‑level inlets (0.1 m above floor) to reinforce buoyancy‑driven natural convection without active fans.